Viver e morrer em São Paulo: a vida, as doenças e a morte na cidade do século XIX - Camargo, Luis Soares de (2007)
In the present thesis we analyse the social relationships in the city of São Paulo in the nineteenth century having in mind the constant presence of disease and death during this period. Source of tensions and arrangements, rich in mental elaborations attempting its elucidation, death is treated here as part of an intricate social mesh existing in a city in permanent transformation. Noticing its greater incidence among the children, the women, the poor and the slaves, we have investigated the probable reasons for this and quantified it in a set of tables that made possible the evaluation of the life expectancy of the inhabitants of de city of São Paulo in the mid nineteenth century. The tables are also used as source for further analyses. Death thus becomes the object of a complex history, ambiguous at times, since it is one of several stages in a process that starts by the contact with disease but does not end with the end of life, for there remains a body that is to become the source of conflicts and appropriations of diverse kinds. These complex social relationships in an interface with the city, with its problems and customs, can only be understood and disclosed when considered in the context of a hierarchical society submitted to several spheres of power and interacting with them. This being so, disease and death will be approached here as social phenomena, objetcs for historical reflexion, not the least because they do not occur secluded from their time, their space, or the individuals that experience them